Bacterial canker of mango: incidence and control - OM PRAKASH, A.K. MISHRA and (Indian Phytopathology, 2012)
Bacterial canker of mango caused by Xaruhomonas campestris pv. mangijeraeindicae appeared in a severe form at the Experimental Research Farm, Rehmankhera, Lucknow during early June 1988. During disease inoculum build up in May, temperature ranged from 17.3-48Â°C, R.H. 25-100 per cent, wind velocity 0.04-8.65 km/h and one rainy day (rainfall-0.8 mm). This indicates that frequent rainfall was not essential for the build up of inoculum. OUl of the 212 cvs, evaluated under natural condition, 95 were found free of infection and the remaining were moderately lO highly susceptible, Higher incidence of disease was recorded from Rehmankhera as compared to Bust i and Suh ar anpur. Of the five chemicals tried, strcptocyc linc (200 ppm) gave best result.